Organochlorines, Organophosphate Bioaccumulation and Reproductive Dysfunction in Fish Captured from Polluted River Gomti during Pre-Monsoon - Nigam, S. K.; Singh, Jyoti; Singh, Ashwarya Luxmi; Das, V. K.; Singh, P. B. (Journal of Ecophysiology and Occupational Health, 2011)
The present investigation was performed to monitor the HCHs (HCH isomers), DDTs (DDT and its metabolites), chlorpyrifos, plasma levels of estradiol-17Î² (E2) and gonadosomatic index (GSI) between the sampling sites of the non-polluted ponds of Gujartal, Jaunpur (reference site) and the polluted river Gomti (Jaunpur), affecting the reproductive physiology of some edible female catfish during pre-monsoon season. The HCHs, DDTs and chlorpyrifos were measured by gas liquid chromatography (GLC) and hormone by Enzyme- Linked Immunosorbent Assay (ELISA). The results indicated that the presence of HCHs, DDTs and chlorpyrifos was very high in the catfish captured from polluted river as compared from the conspecific fish captured from reference site. The GSI and E2 declined in female catfish of polluted site when compared to same species from reference site. Results have also indicated that catfish contained high bioaccumulation of HCHs, DDTs and chlorpyrifos which was beyond permissible limit as compared to the female catfish of the reference site. In conclusion, the fishes of river Gomti were highly polluted when compared with the fish of reference site as was evident from high levels of tissue bioaccumulation of HCHs, DDTs, chlorpyrifos and decreased levels of plasma E2 inhibiting the reproductive physiology of these species at receptor level. However, the levels exceeded maximum residue limits (MRL) as recommended by Codex, hence it is suggested that the fish containing pesticide residues beyond permissible limit should be avoided for the food purposes.